Análise comparativa de modelos de concessão de rodovias no Brasil: um enfoque na segurança viária - Carolina Mara Passos de Moura Mucci (2011)
The grant of roads in Brazil started in the mid 90s. In order to solve the difficulties in financing for the construction, maintenance and conservation of the highways net, the Federal Government and some states transferred the administration and the operation of several stretches of roads to private companies. Each programme was conceived with its own characteristics and showed a unique developmentthroughout the years. In this paper, the types of road grant used in Brazil were described presenting a comprehensive history of the process of transferring the grid with their features and regulatory aspects. Some of the major international grant programmes were shown as well. Based on this survey, the performance of the federal programme and those of São Paulo, Paraná and Rio Grande do Sul states are accessed. Through the traffic volume, investment and accidents indicators it was possible to evaluate the behaviour of each programme regarding road safety in comparison to the situation of the other roads in the national highway net. Moreover, this paper also accesses the grant effects from the implemented improvement, constant maintenance and operation of the stream by the establishment of specific security road measures as: the deployment of guardrails and the resurfacing of roads. After determining the reduction in the number of accidents that may be expected by the establishment of these measures, it was possible to calculate the economic impact resulting from the improvements adopted and compare the situation of road net granted and not granted.